Indonesia Pengaruh Indeks Pembangunan Manusia, Pendapatan Asli Daerah, dan Pengeluaran Pemerintah Terhadap Kemiskinan di Kabupaten Enrekang - muh akmal, akmal; Aisyah, Siti (ICOR: Journal of Regional Economics, 2023)
This study aims to determine the effect of the Human Development Index, Regional Original Income and Government Expenditures on Poverty in Enrekang Regency. The type of research used in this research is quantitative research. The data processed is secondary data from the Human Development Index, Regional Original Income, Government Expenditures and Poverty in Enrekang Regency. The results showed that simultaneously the Human Development Index, Regional Original Income and Government Expenditures had a significant effect on Poverty in Enrekang Regency, this was evidenced by the significance value smaller than the probability (0.000 < 0.05). Partially the Human Development Index has a negative and significant effect on poverty in Enrekang Regency, as evidenced by the significance value being smaller than the significance probability (0.000> 0.05). Regional Original Income partially has a negative and significant effect on Poverty in Enrekang Regency, as evidenced by the significance value is smaller than the significance probability (0.017 > 0.05). And Government Expenditure partially has a negative and insignificant effect on Poverty in Enrekang Regency, as evidenced by the significance value greater than the significance probability (0.252 > 0.05).